Digital nudging: a human component automation tool - Martins, Fernando Jacob Teixeira (2022)
Technological advances make people increasingly use computer systems to perform various actions such as shopping, watching the news, making payments, etc. Through digital nudges, which are the change of the user interface to choose a certain previously determined option, it is possible to implement human component automation tools that facilitate the integration of nudges in different sites. The implementation of nudges on websites is not simple and requires technical knowledge to change the interfaces previously chosen so that users can make choices predetermined by the site managers. Currently, there are no defined methods or tools that help site managers to implement nudges for their users, thus it is intended to take an initial step towards the creation of a tool that allows this first step to be taken and facilitates the implementation of nudges on the various websites without the need of specialized staff to provide nudges. Through the nudging tool we implemented, it is intended to automate the human component so that site managers can add nudges to their websites through a plugin. The addition of a nudge will be done in a simple way and require little technical intervention by the site managers. A plugin was developed in WordPress, through which three nudges were created. To validate the tool that was developed two similar sites (one without nudges and another with nudges) were made available to a set of users and the interaction of users with both sites was collected through Google Analytics. The results show that applying digital nudging through the variation of the default slider and the size variation of the content has changed users’ behavior. On the website with nudges, 75% of the actions performed by users were the intended ones. The website with nudges equally gathered a higher percentage of clicks (more 32.35% in comparison to the no nudges website). The very positive results encourage the continuous use of nudges in digital environments and shed some light to future works.